2018
DOI: 10.1080/15563650.2018.1497172
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of toxic cardiomyopathy

Abstract: Background: Dilated cardiomyopathy is a frequent disease responsible for 40-50% of cases of heart failure. Idiopathic cardiomyopathy is a primary disorder often related to familial/genetic predisposition. Before the diagnosis of idiopathic cardiomyopathy is made, clinicians must not only rule out viral and immune causes, but also toxic causes such as drugs, environmental agents, illicit substances and natural toxins. Objective: The objective of this review is to present recent data on the mechanisms underlying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 99 publications
3
50
0
5
Order By: Relevance
“…Studies in animals have demonstrated that acute and chronic ethanol administration impairs cardiac contractility 112 and decreases the contractile protein α-myosin heavy chain 110 . The metabolite of alcohol, acetaldehyde, can alter cellular calcium, magnesium and phosphate homeo stasis and impair mitochondrial respiration, for example 113 . Damage to the myocardium from alcohol also recruits inflammatory cells to the heart 114 .…”
Section: Chemical and Toxin Exposurementioning
confidence: 99%
“…Studies in animals have demonstrated that acute and chronic ethanol administration impairs cardiac contractility 112 and decreases the contractile protein α-myosin heavy chain 110 . The metabolite of alcohol, acetaldehyde, can alter cellular calcium, magnesium and phosphate homeo stasis and impair mitochondrial respiration, for example 113 . Damage to the myocardium from alcohol also recruits inflammatory cells to the heart 114 .…”
Section: Chemical and Toxin Exposurementioning
confidence: 99%
“…The only transcript specifically affected by EtOH is Pak1 (p21‐activated kinase 1), a critical regulator of p21, a key player in cell cycle exit (Seoane et al., ; Siegenthaler and Miller, ), and target of EtOH (e.g., Hantson, ; Haycock, ). It is noteworthy that, like TGFβ1 receptor (Heldin and Moustakas, ), Pak1 is a serine‐threonine kinase (Bokoch et al., ; Galisteo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…La miocardiopatía alcohólica es a menudo subdiagnosticada, ya que algunos estudios muestran un prevalencia de hasta el 20% de las MCD. El alcohol causa la disfunción sistólica del VI de una manera aparentemente relacionada con la dosis y algunos estudios sugieren reversibilidad tras la abstención (4) . En el caso de las drogas de quimioterapia existen tres tipos diferentes.…”
Section: Tóxicasunclassified
“…La medición de parámetros de función diastólica como llenado ventricular, tamaño auricular, relación E/e' como expresión de presiones de llenado y presión sistólica pulmonar no debe ser olvidada. La mayor disponibilidad en los equipos de tecnología de Doppler tisular así como speckle tracking facilita la caracterización tisular no invasiva (2,4) .…”
Section: Ecocardiogramaunclassified